Achieving interoperability in mobility as a service: a data ecosystem leveraging Semantic Web Technologies - Essawy, Shams Khaled Elhosseny Ghazy (2024)
As urbanization continues to accelerate worldwide, the need for efficient and interconnected transportation systems becomes increasingly critical. Mobility as a Service (MaaS) has emerged as a promising solution to address this challenge by integrating various modes of transportation into a seamless and user-centric experience. However, the success of MaaS hinges on achieving robust interoperability among stakeholders, a task fraught with complexities and disagreements.